The occurrence of cryptosporidiosis and amoebiasis among HIV infected female sex workers with symptomatic diarrhoea - Singh Thongam, Nabakumar; Singh , L. Anand (International Journal of Medical Research and Review, 2020)
Objectives: Manipur is one of the high HIV prevalence states of India.Quite a good number of HIV infected females are indulged in the profession of sex workers. These female sex workers (FSWs) are experiencing a number of gastrointestinal related disorders including diarrhoea caused by a wide variety of pathogens, including parasites. Therefore, the present study is being undertaken with a view assessing the occurrence of enteric parasites, especially Cryptosporidium sp and Entamoeba histolytica towards their involvement as the diarrhoeagenic agent(s) in these groups of patients. Materials and Methods: A cross-sectional study was conducted in the Department of Microbiology, Regional Institute of Medical Sciences (RIMS) Hospital, Imphal, Manipurfrom1stJanuary to 31stDecember 2018.The study group included54 HIVseropositive female sex workers with symptomatic diarrhoea. Stool sample(s) preserved in 2.5% K2Cr2O7for Cryptosporidium sp and 10% buffer formalin for Entamoeba histolytica and other classical parasites were collected for this study. Results: The present study reveals that out of the selected 54 HIV positive FSWs screened for the presence of enteric parasitosis, 16 (29.62%) individuals were found positive for three parasitic infections– cryptosporidiosis, amoebiasis and hookworm infection. Both mixed infection (31.25%) and single infection (68.75%) were observed among the patients. Single infection with Cryptosporidium sp and Entamoeba histolytica were observed in 5 (31.25%) and 6 (37.5%) patients respectively. Patients in the age group of 25 -30 and 30-35 years were observed to have been more infected. Conclusion: The study reveals that intestinal parasitic infection caused by Cryptosporidium sp and Entamoeba histolytica are prevalent among the present study group of HIV infected female sex workers.